Pengembangan Media Pembelajaran Berbantuan Nearpod Terhadap Kemampuan Pemecahan Masalah dalam Materi Statistika Kelas VIII - Maulinisa, Dwi Nurul; Sandie, Sandie; Ardiawan, Yadi (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the level of validity, level of practicality and level of effectiveness of nearpod-assisted learning media on problem solving abilities in statistics material. The research method used in this research is the research and development method. The subjects in this research were divided into two, namely development subjects and product trial subjects. The data collection tools used in this research were validation sheets, questionnaires, and tests. Based on the results of the research that has been carried out, it can be concluded that the learning media assisted by nearpod on problem solving abilities is very valid, very practical, and very effective for use as a learning medium.